1975
DOI: 10.1007/bf01262318
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms, chronic bronchitis, and ventilatory function in shipyard welders

Abstract: SummaryThe prevalence of respiratory symptoms (by standard questionnaire) and the impairment of ventilatory function (vital capacity and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

1983
1983
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
1
11
0
3
Order By: Relevance
“…The risk ratio was within the earlier -re ported range of [2][3][4][5][6][7][8][9][10][11][12][13][14] (10,17,21,29).…”
Section: Chronic Bronchitismentioning
confidence: 97%
“…The risk ratio was within the earlier -re ported range of [2][3][4][5][6][7][8][9][10][11][12][13][14] (10,17,21,29).…”
Section: Chronic Bronchitismentioning
confidence: 97%
“…Industrial Health 2000, 38, 69-78 steel were highest, leveling off at 10 mg/m 3 , during the tungsten inert gas welding (TIG) operation on aluminum or stainless steel were lowest, leveling off at 1-2 mg/m 3 . Wal 9) showed that the average concentrations of fumes were 5.3 mg/m 3 for MMA on mild steel, 4.4 mg/m 3 for MIG/MAG (metal active gas) welding on mild steel and 1.4 mg/m 3 for TIG welding on stainless steel, and that the highest concentration of Cr(VI) was 1.5 mg/m 3 , and highest concentration of nickel was 0.21 mg/m 3 for MMA on stainless steel.…”
Section: % Of Vital Capacities (Vmentioning
confidence: 99%
“…Wal 9) showed that the average concentrations of fumes were 5.3 mg/m 3 for MMA on mild steel, 4.4 mg/m 3 for MIG/MAG (metal active gas) welding on mild steel and 1.4 mg/m 3 for TIG welding on stainless steel, and that the highest concentration of Cr(VI) was 1.5 mg/m 3 , and highest concentration of nickel was 0.21 mg/m 3 for MMA on stainless steel. Ohmori et al 7) showed that the mean concentration of O 3 at a breathing zone was 1.27 ppm for MIG on aluminum and 0.28 ppm for CO 2 arc welding on mild steel.…”
Section: % Of Vital Capacities (Vmentioning
confidence: 99%
See 2 more Smart Citations